A cross-sectional study of 'yaws' in districts of Ghana which have previously undertaken azithromycin mass drug administration for trachoma control. - Rosanna Ghinai; Philip El-Duah; Kai-Hua Chi; Allan Pillay; Anthony W Solomon; Robin L Bailey; Nsiire Agana; David C W Mabey; Cheng-Yen Chen; Yaw Adu-Sarkodie; Michael Marks (PLoS Neglected Tropical Diseases)
Yaws, caused by Treponema pallidum ssp. pertenue, is reportedly endemic in Ghana. Mass distribution of azithromycin is now the cornerstone of the WHO yaws eradication campaign. Mass distribution of azithromycin at a lower target dose was previously undertaken in two regions of Ghana for the control of trachoma. Ongoing reporting of yaws raises the possibility that resistance may have emerged in T. pallidum pertenue, or that alternative infections may be responsible for some of the reported cases. We conducted a cross-sectional survey in thirty communities in two districts of Ghana where MDA for trachoma had previously been conducted. Children aged 5-17 years with ulcerative lesions compatible with yaws were enrolled. Samples for treponemal serology and lesion PCR were collected from all children. 90 children with 98 lesions were enrolled. Syphilis serology was negative in all of them. PCR for T. pallidum ssp pertenue was negative in all children, but Haemophilus ducreyi DNA was detected in 9 lesions. In these communities, previously treated for trachoma, we found no evidence of ongoing transmission of yaws. H. ducreyi was associated with a proportion of skin lesions, but the majority of lesions remain unexplained. Integration of diagnostic testing into both pre and post-MDA surveillance systems is required to better inform yaws control programmes.